AN OVERVIEW ON USER-GENERATED CONTENT AND THE EMPOWERMENT OF ONLINE TRAVELLERS - Mendes Filho, Luiz Augusto Machado; Tan, Felix B. (Revista UNI-RN, 2009)
The World Wide Web has empowered travellers, enabling them to exchange opinions or experiences with others, and consequently, influencing their travel decisions. For example, user-generated content (UGC) is allowing Internet users to make comments and reviews in a large variety of forms such as photos, videos, podcasts, ratings, reviews, articles and blogs. The empowerment provided by these UGC tools has changed the dynamics of the travel industry. This paper presents an overview of some important concepts of UGC and the empowerment of travellers on the World Wide Web.